Сarcinogenic substances in the atmospheric air of Dnipro city and risk to the population - Serdiuk , A.M.; Chernychenko , I.O.; Lytvychenko , O.M.; Babii , V.F.; Kondratenko , O.Ye.; Hlavachek , D.O. (Medicni Perspektivi, 2021)
The objective – to study the dynamic changes for the health risk of the population of the industrial center in accordance with the state of atmospheric air pollution with carcinogenic compounds. The assessment of the state of atmospheric air pollution was carried out by us based on the results of physicochemical analysis of samples taken in places attached to the locations of stationary posts of state monitoring. The concentration of identified substances was determined by conventional methods: spectral-luminescent and gas chromatographic. Heavy metal concentrations were determined using data from the Central Geophysical Observatory of the Ministry of Emergency Situations. The calculation of the inhalation load of chemical carcinogens and the risks associated with them (non-carcinogenic and carcinogenic) was carried out in accordance with domestic guidelines. The assessment of dynamic changes in the nature of atmospheric air pollution with a complex of carcinogenic substances was made 5 of them are constantly recorded at levels exceeding hygienic standards. When compared with the reference concentrations, all compounds are characterized by high coefficients, indicating the likelihood of their effect on the body's immune system, respiratory organs, malformations, etc. A high individual carcinogenic risk of the effect of chromium VI and nitrosamines was determined. A total carcinogenic risk is formed at levels of 2.5 – 3.9×10-3, which should be considered as high; this requires development and implementation of preventive measures. On the territory of the industrial center, a high level of air pollution with increased carcinogenic and non-carcinogenic risk is stably registered.